Pelatihan Menulis Kreatif bagi Siswa Sanggar Bimbingan di Pondok An-Nahdloh Selangor, Malaysia - Syamsul Ghufron; Nafiah Nafiah; Fifi Fitriyah; Pance Mariati; Tiyas Saputri; Rudi Susanto (IKIP PGRI Bojonegoro, 2024)
ABSTRACTWriting skills require continuous and intensive training until beautiful writing and aesthetic value are produced. Writing skills must be developed in the world of education because they can train students to think critically. Creative writing training for Guidance Studio Students at Pondok An-Nahdloh Selangor, Malaysia aims to (1) familiarize students with literacy culture, (2) teach students to have literacy skills, especially creative writing skills, especially poetry in Indonesian, (3) motivate students to write creatively in everyday life, (4) assist teachers in teaching literacy skills. The partner for this community service activity is Pondok An-Nahdloh Selangor, Malaysia. The method of this activity is training and mentoring partners with stages of socialization, lectures on poetry writing methods, poetry writing practice, and mentoring poetry improvements. The results of this service can be concluded that this training and mentoring activity was very successful and was able to improve the creative writing skills of the training participants.Keywords: Training, creative writing, guidance studio students, pondok An-NahdlohABSTRAKKeterampilan menulis memerlukan pelatihan terus-menerus dan intensif sampai dihasilkan tulisan yang indah dan memiliki nilai estetika. Keterampilan menulis harus ditumbuhkembangkan dalam dunia pendidikan karena dapat melatih siswa berpikir kritis. Pelatihan menulisan kreatif bagi Siswa Sanggar Bimbingan di Pondok An-Nahdloh Selangor, Malaysi bertujuan untuk (1) mengakrabkan peserta didik dengan budaya literasi, (2) membelajarkan peserta didik agar memiliki keterampilan literasi khususnya keterampilan menulis kreatif khususnya puisi dalam bahasa Indonesia, (3) memotivasi peserta didik untuk menulis kreatif dalam kehidupan sehari-hari, (4) membantu tugas para guru dalam membelajarkan keterampilan literasi. Mitra kegiatan pengabdian masyarakat ini adalah Pondok An-Nahdloh Selangor, Malaysia. Metode kegiatan ini yaitu pelatihan dan pendampingan mitra dengan tahapan sosialisasi, ceramah tentang metode penulisan puisi, praktik menulis puisi, dan pendampingan perbaikan puisi. Hasil pengabdian ini dapat disimpulkan bahwa kegiatan pelatihan dan pendampingan ini sangatlah berhasil dan mampu meningkatkan kemampuan menulis kreatif para peserta pelatihan.Kata Kunci: Pelatihan, menulis kreatif, siswa sanggar bimbingan, pondok An-Nahdloh